Lean Product Management : Successful products from fuzzy business ideas. - Nandakumar, Mangalam (Packt Publishing, 2018)
Lean Product Management is a handy guide for product managers and anyone embarking on new product development. This book will help readers to align their product strategy by identifying the most viable product, setting up and measuring time-bound metrics, developing a clear product roadmap, and eliminating waste.